\[\boxed{\text{668\ (668).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ 2\text{ab} - 3ab^{2} = \text{ab} \cdot (2 - 3\text{ab})\]
\[2)\ 8x^{4} + 2x³ = 2x³(4x + 1)\]
\[3)\ 12a²b² + 6a²b³ + 12a²b³ =\]
\[= 6ab²(2a + ab + 2b)\]
\[4)\ 2a - 2b + ac - bc =\]
\[= 2 \cdot (a - b) + c \cdot (a - b) =\]
\[= (a - b)(2 + c)\]
\[5)\ m² - mn - 4m + 4n =\]
\[= m(m - n) - 4 \cdot (m - n) =\]
\[= (m - n)(m - 4)\]
\[6)\ ax - ay + cy - cx - x + y =\]
\[= (ax - cx - x) - (ay - cy - y) =\]
\[= x(a - c - 1) - y(a - c - 1) =\]
\[= (a - c - 1)(x - y)\]
\[\boxed{\text{668.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ m^{4} - 625 =\]
\[= \left( m^{2} - 25 \right)\left( m^{2} + 25 \right) =\]
\[= (m - 5)(m + 5)(m^{2} + 25)\]
\[2)\ x^{16} - 81 =\]
\[= \left( x^{8} - 9 \right)\left( x^{8} + 9 \right) =\]
\[= (x^{4} - 3)(x^{4} + 3)(x^{8} + 9)\]
\[3)\ 2^{4n} - 16 =\]
\[= \left( 2^{2n} - 4 \right)\left( 2^{2n} + 4 \right) =\]
\[= (2^{n} - 2)(2^{n} + 2)(2^{2n} + 4)\]